PENDIDIKAN KARAKTER BAGI ANAK USIA DINI MELALUI BUKU CERITA BERGAMBAR - Ashiong Parhehean Munthe; Dellya Halim (Satya Widya, 2019)
The picture-story book that emphasize character values in accordance with the vision and mission of Santa Theresia Jakarta Kindergarten is very urgent to develop, because at school, character education books are not available with the value of servite et amate. This was revealed by a teacher through an interview. Based on observations, it was also found that there was indeed no character education book that was in accordance with the school's vision and mission. Character education or moral education in the present context, really needs to be taught and developed, so that children's morals can be formed early. Picture-story book is a book in which there are stories, characters, grooves, backgrounds, themes that are expressed in the form of writings and images that become one unit. Through reading books, it is easier for children to understand the contents and practical examples to apply the character values that they want to teach. This study uses descriptive qualitative methods. The qualitative descriptive is an attempt to explain facts, data, or objects qualitatively in the form of language or discourse by interpreting them appropriately and systematically. Data collection techniques used were interview and observations. This research was conducted at the Santa Theresia Jakarta Kindergarten. The results of the study indicated that picture-story books that were in accordance with the values of servite et amate needed to be created and developed, in order to help children in early childhood easily understood examples of character actions that must be performed. Therefore, schools need to facilitate and fully support, so that kindergarten teachers are given space and opportunities to develop pictorial story books. The content of the story, character, plot, language, selection of diction, choosing the color of the image must be relevant for early childhood.